Highly Stereodivergent Construction of a C2-Symmetric cis, cis- and trans, trans-2,6-Dioxabicyclo[3.3.0]octane Framework by Double Intramolecular Amide Enolate Alkylation: Total Synthesis of (+)-Laurenidificin and (+)-Aplysiallene - Shin, Iljin; Jang, Hongjun; Kwak, Soo Yeon; Park, Youngjik; Lee, Dongjoo; Kim, Hyoungsu; Kim, Deukjoon (Organic Letters, 2022)
The highly stereoselective construction of C2-symmetric cis,cis- and trans,trans-2,6-dioxabicyclo[3.3.0]octane (fused bis-tetrahydrofuran) skeletons 4a and 4b has been accomplished via a novel stereodivergent double intramolecular amide enolate alkylation of common cyclization substrate 5 through the judicious choice of "chelate"versus crown ether-promoted "nonchelate"control. Application of this methodology has provided access to substrate-controlled concise total syntheses of (+)-laurenidificin (3) and (+)-aplysiallene (ent-2), which possess cis/cis- and trans/trans-fused bis-tetrahydrofuran cores, respectively.
Keywords: Amides